COMPREHENSIVE MIDWIFERY CARE IN NY “F” WITH NORMAL PREGNANCY AT THE HEALTH CENTER TANETE BULUKUMPA DISTRICT BULUKUMBA DISTRICT SEPTEMBER - DECEMBER PERIOD YEAR 2024 - Sri Eka Juniarli; Nabila (Jurnal Life Birth, 2025)
Pregnancy, childbirth and postpartum are normal processes. However, you must be careful about this situation so that it does not become a complication. Complications that often occur in pregnant women are anemia, chronic energy deficiency (CED), bleeding, hypertension that continues during childbirth, postpartum, and family planning services. Therefore, efforts are made to provide comprehensive midwifery care. The aim is to provide comprehensive care to Mrs "F" aged 37 years from pregnancy, childbirth, BBL, postpartum, neonate to contraceptive services. The method used is a case study with a Varney midwifery management approach. Through observation, interviews, physical examination and documentation studies. The results of comprehensive midwifery care for Mrs "F" with a normal pregnancy were known from the results of observations which indicated that there were no problems since midwifery care was carried out starting from 33 weeks 3 days of gestation until the birth of the third child with the continuation of labor resulting in retained placenta with the treatment given being injection. second oxytocin and install an infusion of RL ± 500 Ml drips of oxytocin 20 IU/20 tpm, the baby was born with BB: 2450 gr, PB: 47 cm, male gender, postpartum progressed and the neonate walked normally and the contraception used was the DMPA contraceptive . The conclusion is that comprehensive midwifery care for Mrs "Y" was carried out according to midwifery care standards with the result that complications occurred, namely placental retention during labor. However, this situation can be overcome according to the management of retained placenta. Keyword : Comprehensive Midwifery Care